Inferior Meatus Augmentation Procedure (IMAP) to Treat Empty Nose Syndrome: A Pilot Study. (14th January 2020) - Thamboo, Andrew; Dholakia, Sachi S.; Borchard, Nicole A.; Patel, Vishal S.; Tangbumrungtham, Navarat; Velasquez, Nathalia; Huang, Zhenxiao; Zarabanda, David; Nakayama, Tsuguhisa; Nayak, Jayakar V.
Abstract : Our understanding of empty nose syndrome (ENS) continues to evolve. Prior studies evaluating airway augmentation to treat ENS did not use validated disease‐specific questionnaires, making the true impact of these surgeries unclear. We present a case series of 10 patients with ENS (11 procedures) who underwent the inferior meatus augmentation procedure (IMAP) between September 2014 and May 2017. Subjective outcomes of IMAP included comparisons of preoperative and postoperative assessments (1 week, 1 month, 3 months, 6 months) using the Empty Nose Syndrome 6‐item Questionnaire (ENS6Q), Patient Health Questionnaire–9 (PHQ‐9), Generalized Anxiety Disorder 7‐item Scale (GAD‐7), and Sino‐Nasal Outcome Test–22 (SNOT‐22). The decrement in ENS6Q scores observed maintained statistical significance at 6 months ( P ≤. 001). Similar results were achieved with PHQ‐9, GAD‐7, and SNOT‐22 ( P ≤. 01, P ≤. 01, P ≤. 001, respectively). IMAP can dramatically improve the quality of life of ENS patients regarding both ENS‐specific symptoms and psychological well‐being.